Unveiling mysteries against “God of the Gaps” through scientific breakthroughs: an investigation on the arguments of human and Adamic exceptionalism = Membongkar misteri terhadap 'God of the Gaps' melalui penemuan saintifik: satu siasatan terhadap hujah pengecualian manusia dan Adam - Hasan, Md Maruf; Ali, Mohd Mumtaz; Abdul Rahim, Adibah (USIM PRESS, 2025)
Darwin’s single idea, namely the evolution of species, is taking strong ground in every field of scientific research in contemporary times. From the quantum fluctuation of nothingness, scientists have investigated and tried to grasp the evolution of our current universe using an evolutionary perspective. Consequently, we are witnessing that the perception of “God of the Gaps” is being replaced by new scientific discoveries. Richard Dawkins wrote the book entitled, The Ancestor Tale: A Pilgrimage to the Dawn of Evolution’. Dawkins showed in that book how the Pilgrimage of organisms took place on this planet, propounding the evolutionary perspective. All religions and ideologies are now affected by the evolutionary perspective. What would be the future implications for religions (especially Islam) if the notion of “God of the gaps” is filled up with experimental data? Will human exceptionalism and Adamic exceptionalism, along with creationism, be just sophistry for theologians and philosophers as scientific research progresses? This research uses qualitative methodology to understand the future ethical implications of Islam in secular narratives. The research finds that Islamic literature produces abstract and ambiguous literature regarding the evolutionary perspective. This research suggests that ambiguity in Islamic narratives can potentially hamper and create confusion among Muslim youths